There Is No One Way to Teach Math : Actionable Ideas for Grades 6-12 - Picciotto, Henri; Pemantle, Robin ([Place of publication not identified] : Routledge, 2024)
A collaboration between a seasoned math teacher and a research mathematician, this resource offers balanced instructional ideas based on student intellectual engagement and skilled teacher leadership. It is solidly grounded in many areas of classroom practice, but rather than serving as a prescriptive how-to manual, the authors invite reflection and discussion across classrooms and math departments, much in the way you would share ideas in the teachers' lounge or across the table at a conference. Chapters offer practical suggestions and concrete examples to teachers of grades 6-12 on just about every aspect of the job: manipulatives, technology, lesson planning, group work, classroom discussion, and more. In opposition to the idea of a "one-size-fits-all" curriculum, the authors explain how to integrate teaching techniques: formal and informal, student-centered and teacher-led, experiential and rigorous. Chapters also include vignettes, as well as many links to curricular materials. Ideal for math educators of grades 6-12, this book is both comprehensive in its strategies and sensitive to the complexities of teaching. For these reasons, math departments, coaches, teacher leaders, and faculty at other levels can also easily reference its content where relevant. This book offers multiple entry points for teachers and departments to discuss and enhance their practice, making it essential reading for any math classroom or professional development opportunity.
Introduction Part 1: Pedagogical Principles 1. Philosophical Framework 2. Problem Solving 3. Different Modes Part 2: Classroom Practice 4. Cooperative Learning 5. Learning Tools 6. Manipulatives 7. Computation Engines 8. Leading Discussions Part 3: The Big Picture 9. Extending Exposure 10. Planning 11. Assessment 12. Making Change
Keywords: Mathematics -- Study and teaching (Secondary); EDUCATION / General; EDUCATION / Teaching Methods & Materials / Mathematics; EDUCATION / Secondary